ANALISIS KELAYAKAN PENGEMBANGAN USAHA YUJAMU HERBAL JUICE DI KABUPATEN PURWOREJO - Agus Fitri Yanto; Endah Aisyiyah Ningrum (JURNAL EKONOMI DAN TEKNIK INFORMATIKA, 2021)
Micro, Small and Medium Enterprises (MSMEs) in the field of herbal drinks have developed quite significantly. One of the herbal drinks MSME products in Purworejo is YUJAMU Herbal Juice. This qualitative and quantitative research is related to the feasibility analysis of business development which aims to find out whether the YUJAMU Herbal Juice business is feasible to develop. Data collection techniques used include observation, documentation, and literature study. The results of this study show positive results for market, legal, human resources aspects, social and economic aspects, environmental aspects, and financial aspects. The result of the calculation using the Payback Period (PBP) method is one year 5 months, Net Present Value (NPV) is IDR 381.496, the value of Break Event Point Unit (BEP Unit) is 46 bottles of YUJAMU Herbal Juice sour sugar, 70 bottles of YUJAMU Herbal Juice turmeric acid, and 55 bottles of YUJAMU Herbal Juice infused water. And the rupiah BEP for YUJAMU Herbal Juice sour sugar is Rp. 81,526, YUJAMU Herbal Juice is sour turmeric IDR 102,800, and YUJAMU Herbal Juice infused water is IDR 81,526. Based on these data, it can be concluded that the YUJAMU Herbal Juice business is quite feasible to be developed.